2018
DOI: 10.1519/jsc.0000000000002387
|View full text |Cite
|
Sign up to set email alerts
|

Positional Differences in GPS Outputs and Perceived Exertion During Soccer Training Games and Competition

Abstract: Soccer training games are popular training modalities, allowing technical, tactical, and physical aspects to be trained simultaneously. Small (SSGs), medium (MSGs) and large training games (LSGs) elicit differing physical demands. To date, no research has investigated physical and perceived demands of training games upon soccer playing positions relative to competitive demands. Additionally, previous research has referenced average competitive intensities, ignoring peak demands of competition. The current aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 32 publications
4
54
0
4
Order By: Relevance
“…In particular, Vázquez-Guerrero et al (2019) showed that basketball players averaged 1.8 and 1.5 high-intensity accelerations and decelerations and covered a relative distance of 72.6 m min −1 . A similar trend has been observed in previous studies conducted in other sports, such as associated football (Abbott et al, 2018;Delaney et al, 2018;Martín-García et al, 2018;Casamichana et al, 2019), rugby (Delaney et al, 2016;Cunningham et al, 2018), Gaelic football (Malone et al, 2017), and Australian football (Delaney et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, Vázquez-Guerrero et al (2019) showed that basketball players averaged 1.8 and 1.5 high-intensity accelerations and decelerations and covered a relative distance of 72.6 m min −1 . A similar trend has been observed in previous studies conducted in other sports, such as associated football (Abbott et al, 2018;Delaney et al, 2018;Martín-García et al, 2018;Casamichana et al, 2019), rugby (Delaney et al, 2016;Cunningham et al, 2018), Gaelic football (Malone et al, 2017), and Australian football (Delaney et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…While some studies have determined the most demanding scenarios in physical demands during competition in intermittent team sports such as association football (Abbott et al, 2018;Delaney et al, 2018;Martín-García et al, 2018;Casamichana et al, 2019), rugby (Delaney et al, 2016;Cunningham et al, 2018), Gaelic football (Malone et al, 2017), and Australian football (Delaney et al, 2017) through different time average rolling durations, no studies are available that quantify physical demands during match play in basketball using this approach. A plethora of studies have examined the average (mainly per minute) and absolute physical demands of match play in basketball reporting that players usually cover 5-6 km at an average speed of 70-90 m min −1 and perform a total of 40-50 jumps (Stojanović et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the systematic phases of the microcycle are very unique to this club philosophy and would provide added insight to practitioners. Additional studies are also needed detailing loading patterns and training practices from various European competitions, given that the body of evidence is primarily from English Premier League clubs (1,4,35). This is relevant because differences in culture and competition demands across leagues could result in distinct loading variations in an attempt to optimize performance (e.g., styles of play, number of games, and midseason breaks).…”
Section: Introductionmentioning
confidence: 99%
“…Individualized speed zones rely on fitness test data, such as measures of cardiorespiratory fitness. Thus, recent studies have adopted incremental field tests to indirectly compute athletes' maximal aerobic speed (MAS) (Abbott et al, 2017;Fitzpatrick et al, 2018). MAS is very strongly correlated to maximal oxygen uptake and, in conjunction with maximal sprinting speed (MSS), allows calculation of the anaerobic speed reserve (ASR) that accounts for the transition from high-speed running to sprinting (Hunter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%